2009
DOI: 10.5194/angeo-27-631-2009
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of 2-day wave in the E-region electric fields and their relationship to winds and ionospheric currents

Abstract: Abstract.We analyze the effects of the 2-day wave activity in the EEJ using one coherent scatter radar and eight magnetometer stations located close to the dip equator. The wavelet analysis of the magnetometer data reveals a 2-day signature in the semidiurnal geomagnetic tide. The E-region zonal background ionospheric electric field, derived from coherent radar measurements, shows 2-day oscillations in agreement with such oscillations in the magnetometers data. An anticorrelation between the amplitude of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…This wavelike current system produces perturbations in the geomagnetic field that are easily measured at ground level. Then, the day-to-day variability in the ionospheric currents detected by ground-based magnetometer measurements particularly during magnetically quiet conditions, could be due to penetration of planetary waves or modulated tides into the dynamo region (Gurubaran et al, 2001;Pancheva et al, 2006Pancheva et al, , 2008Aveiro et al, 2009;Ramkumar et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This wavelike current system produces perturbations in the geomagnetic field that are easily measured at ground level. Then, the day-to-day variability in the ionospheric currents detected by ground-based magnetometer measurements particularly during magnetically quiet conditions, could be due to penetration of planetary waves or modulated tides into the dynamo region (Gurubaran et al, 2001;Pancheva et al, 2006Pancheva et al, , 2008Aveiro et al, 2009;Ramkumar et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These perturbations appear to be strongest during SSW events Pancheva et al [2006]. studied in detail the global occurrence of 2 day wave activity during this period, andAveiro et al [2009] reported their signatures on the equatorial electrojet and E region electric fields in the Brazilian sector.…”
mentioning
confidence: 99%
“…Finally, the phase velocity estimates for Type II irregularities ( V pII , in m/s), which were obtained by the fitting procedure, are used to calculate the vertical electric field ( E z ), as given by: where ϕ is the beam zenith angle (30° eastward), H is the horizontal component of the magnetic flux density B , and B is defined as ∣ B ∣. For a more complete explanation about the E z computation, see Aveiro et al [2009].…”
Section: Experiments and Data Analysis Techniquementioning
confidence: 99%
“…where f is the beam zenith angle (30°eastward), H is the horizontal component of the magnetic flux density B, and B is defined as jBj. For a more complete explanation about the E z computation, see Aveiro et al [2009].…”
Section: Experiments and Data Analysis Techniquementioning
confidence: 99%